18F-FDG-PET CT features of colo-colic intussusceptions in patient with colonic carcinoma - Ahmad Saad, Fathinul Fikri; Abdullah, Noraini Sarina; Samat, Shahrin; Nordin, Abdul Jalil (Universiti Putra Malaysia Press, 2016)
Colo-colic intussusception is a rare manifestation of a primary tumour in an adult patient. This article aims to document the rarity of colo-colic intussusception features on the 18 FDG-PET-CT in a patient with primary colonic carcinoma. An 18 FDG-PET-CT was performed for the purpose of pretreatment staging of a colonic carcinoma in a 61-year-old man following a diagnostic colosnoscopic biopsy. He presented with abdominal distension and peri-rectal bleeding for a month. The fused 18 F-FDG PET-CT image revealed an FDG-avid mass in the left hemicolon showing a rim of FDG avidity denoting the head of intussusceptum. There are also multiple FDG-avid nodules seen along the anti-mesenteric colonic fat suspicious for lymph nodes metastasis. Debulking of tumour revealed a mucinous adenocarcinoma of colon with a metastatic lymph node. 18 FDG PET-CT features of intussusception in colonic carcinoma have never been described before. It can potentially become a preferred diagnostic tool in delineating a potential tumour mass within the intussusceptions that help improve prognosis in patients with malignancy.